Differential Impacts of the Head on Platynereis dumerilii Peripheral Circadian Rhythms - Arboleda, Enrique; Zurl, Martin; Waldherr, Monika; Tessmar-Raible, Kristin (Frontiers in Physiology, 2019)
The marine bristle worm Platynereis dumerilii is a useful functional model system for the study of the circadian clock and its interplay with others, e.g. circalunar clocks. The focus has so far been on the worm’s head. However, behavioral and physiological cycles in other animals typically arise from the coordination of circadian clocks located in the brain and in peripheral tissues. Here we focus on peripheral circadian rhythms and clocks, revisit and expand classical circadian work on the worm’s chromatophores, investigate locomotion as read-out and include molecular analyses. We establish that different pieces of the trunk exhibit synchronized, robust oscillations of core circadian clock genes. These circadian core clock transcripts are under strong control of the light-dark cycle, quickly losing synchronized oscillation under constant darkness, irrespective of the absence or presence of heads. Different wavelengths are differently effective in controlling the peripheral molecular synchronization. We have previously shown that locomotor activity is under circadian clock control. Here we show that upon decapitation worms exhibit strongly reduced activity levels. While still following the light-dark cycle, locomotor rhythmicity under constant darkness is less clear. We also observe the rhythmicity of pigments in the worm’s individual chromatophores, confirming their circadian pattern. These size changes continue under constant darkness, but cannot be re-entrained by light upon decapitation. Our works thus provides the first basic characterization of the peripheral circadian clock of Platynereis dumerilii. In the absence of the head, light is essential as a major synchronization cue for peripheral molecular and locomotor circadian rhythms, while circadian changes in chromatophore size can continue for several days in the absence of light/dark changes and the head. Thus, in Platynereis the dependence on the head depends on the type of peripheral rhythm studied. These data show that peripheral circadian rhythms and clocks should also be considered in "non-conventional" molecular model systems, i.e. outside Drosophila melanogaster, Danio rerio and Mus musculus, and build a basic foundation for future investigations of interactions of clocks with different period lengths in marine organisms.